Psychometric evaluation of the Persian version of the Family Caregiver-Specific Quality of Life Scale (FAMQOL) among family caregivers of patients with chronic psychiatric disorders - Seyedmohammad Mirhosseini; Fatemeh Moslemi; Hamid Sharif-Nia; Somaye Minaei-Moghadam; Mahboobeh Khajeh; Ali Abbasi; Hossein Ebrahimi (BMC Psychology)
Abstract Background Family caregivers of psychiatric patients often experience various negative psychosocial consequences, with a decline in quality of life being the most prevalent. This study was conducted with the aim of evaluating the psychometric indices of the Persian version of the Family Caregiver-Specific Quality of Life Scale (FAMQOL). Methods This cross-sectional study was conducted in 400 family caregivers of patients with chronic psychiatric diseases in Iran in 2024 using convenience sampling. Using a forward-backward translation procedure, the face and content validity of the FAMQOL were assessed through both qualitative and quantitative methods. After face and content validity, in order to determine construct validity, exploratory (n = 200) and confirmatory (n = 200) factor analysis was performed. To determine reliability, internal consistency (Cronbach’s alpha coefficient and Macdonald’s omega coefficient) and stability (intraclass correlation coefficient) were estimated. Results A total of 400 participants were evaluated, comprising 184 males (46.0%) and 216 females (54.0%). In content validity, one item was removed and during exploratory factor analysis, the remaining 15 items were loaded on four factors including social, spiritual, physical and psychological, which described 61.74% of the total variance. Confirmatory factor analysis showed that the obtained model has a good fit. All obtained factors had convergent and discriminant validity. Cronbach’s alpha (0.783 to 0.932), Macdonald’s omega (0.817 to 0.934) and intraclass correlation coefficients (0.953 to 0.971) showed acceptable internal consistency and stability of the factors of the Persian version of FAMQOL. Conclusion Findings from this study confirm that the Persian version of the FAMQOL is a valid and reliable instrument for evaluating the quality of life among family caregivers of patients with chronic psychiatric disorders. This scale holds significant potential for both research and clinical applications, facilitating the identification of caregivers’ needs and guiding the creation of targeted interventions to enhance their quality of life.